Culture of Penaeus monodon in freshwater ponds - Ramanathan, N; Padmavathy, p; Francis, T; Athithan, S (Indian Journal of Fisheries, 2011)
The present paper deals with the culture of Penaeus monodon under extensive and semi- intensive systems in freshwater condition. The P.monodon seeds (PL 20) were stocked at the rate of 4000 and 15,000 no. / 0.1 ha under extensive and semi-intensive systems respectively. Under extensive system, the production was 48.400 kg / 0.1 ha / crop in 117 days of culture with an average body weight of 22.0 g and survival rate of 55%. Under semi- intensive system the production was 141.450 kg / 0.1 ha/ crop in 125 days of culture with an average body weight of 20.50 g and survival rate of 46 %. The performance of P. monodon achieved during this trial regarding survival and growth is satisfactory. The water quality parameters under fresh water condition yielded satisfactory production of P. monodon